Thoracoscopy in Pleural Malignant Mesothelioma Diagnosis. Issue 3 (1997) - Tassi, G. F.; Marchetti, G. P.; Fattibene, F.; Chiodera, P. L.
Abstract : On the basis of our personal experience in 70 cases (66 pleural effusions) observed during the period January 1984- January 1996 we are here illustrating and discussing the diagnostic role of thoracoscopy in malignant pleural mesothelioma. A histological diagnosis was achieved in 94.2% of cases. The endoscopic appearance was clearly neoplastic (masses, nodules) in 53 patients (75.7%) and simply inflammatory in 17 pachypleuritis in 13 (18.6%) and of diffuse hyperemia in 3 (5.7%). In all cases fluid cytology (diagnostic yield: 18.5%) and needle biopsy (diagnostic yield 17.1%) were performed. The extension of pleural involvement (endoscopic staging according to Boutin) was also determined. In 16 patients (22.8%) a parietal and diaphragmatic involvement (stage Ia) was found. In 40 patients (57.2%) an associated visceral invasion (stage Ib). In 14 cases (20%) a diffuse parietal, visceral and mediastinal extension (stage II). The exam has always been well tolerated with few immediate complications: subcutaneous emphysema (4 cases) and some negligeable parietal bleeding (2 cases).